A Fixed-Bed Column Study for Removal of Organic Dyes from Aqueous Solution by Pre-Treated Durian Peel Waste - Nguyen Thi Thuong; Nguyen Thi Tuyet Nhi; Vo Thi Cam Nhung; Hoang Ngoc Bich; Bui Thi Phuong Quynh; Long Giang Bach; Nguyen Duy Trinh (Universitas Gadjah Mada, 2019)
A number of harmful effects on the ecosystem, the life of humankind, and living species caused by dye-contaminated wastewater have urged the development for an efficient and cost-efficient treatment method for colored effluents. The cellulose-based adsorbents have been considered as a facile and efficient approach to remove hazardous pollutants because of the abundance of inexpensive agricultural wastes in Viet Nam. This study aims to investigate the elimination of methylene blue (MB) and crystal violet (VL) from wastewater using a fixed-bed column of pre-treated durian peel. Examined variables in the process are bed depths (2–6 cm), flow rate (5–20 mL/min), and influent dye concentrations (200–600 mg/L). The highest adsorption amount of pre-treated DP was 235.80 mg/g and 527.64 mg/g, respectively, on a 600 mg/L of methylene blue and crystal violet achieved within a bed height of 4 cm and a flow rate of 10 mL/min. Accordingly, the breakthrough curves were constructed and modeled using the relevant theoretical models under the effects of different experimental conditions. Pre-treated durian peel was found to exhibit high adsorption capacity for cationic dye in an initial concentration of 200–600 mg/L with complete removal being obtained.